2016
DOI: 10.1021/acs.biomac.5b01669
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular GAG-like Self-Assembled Glycopeptide Nanofibers Induce Chondrogenesis and Cartilage Regeneration

Abstract: Glycosaminoglycans (GAGs) and glycoproteins are vital components of the extracellular matrix, directing cell proliferation, differentiation, and migration and tissue homeostasis. Here, we demonstrate supramolecular GAG-like glycopeptide nanofibers mimicking bioactive functions of natural hyaluronic acid molecules. Self-assembly of the glycopeptide amphiphile molecules enable organization of glucose residues in close proximity on a nanoscale structure forming a supramolecular GAG-like system. Our in vitro cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 46 publications
1
58
0
Order By: Relevance
“…The results confirmed that ADSCs and TGF- β 1 can inhibit the expression of these two proteins to a certain extent, which can also indicate that ADSCs play a role in promoting the regeneration of cartilage. In the present study, we confirmed that ADSCs can promote the release of GAG, and SOX9, PGC-1 α , and a series of cartilage regeneration marker proteins [2932] expression in chondrocytes can be promoted by coculture with ADSCs. This further showed that ADSCs can not only promote the proliferation of cartilage cells, but also have a protective effect on the regeneration of cartilage cells and this effect is similar to that of TGF- β 1.…”
Section: Discussionsupporting
confidence: 81%
“…The results confirmed that ADSCs and TGF- β 1 can inhibit the expression of these two proteins to a certain extent, which can also indicate that ADSCs play a role in promoting the regeneration of cartilage. In the present study, we confirmed that ADSCs can promote the release of GAG, and SOX9, PGC-1 α , and a series of cartilage regeneration marker proteins [2932] expression in chondrocytes can be promoted by coculture with ADSCs. This further showed that ADSCs can not only promote the proliferation of cartilage cells, but also have a protective effect on the regeneration of cartilage cells and this effect is similar to that of TGF- β 1.…”
Section: Discussionsupporting
confidence: 81%
“…This gel is nontoxic in various cell lines, an important step toward utilization in vivo. Additionally, both in vitro and in vivo differentiation of mesenchymal stem cells into chondrocytes without the use of exogenous growth factors was reported in hyaluronate and heparin mimicking PA hydrogels …”
Section: Supramolecular Bonding Motifsmentioning
confidence: 99%
“…It was also shown in the study of Yaylaci et al hyaluronic acid mimetic self-assembled peptide nanofiber gels enhance the chondrogenesis of MSCs and cartilage regeneration (Fig. 7.3) (Ustun Yaylaci et al 2016). As such, selfassembled peptide gels have recently emerged as a class of next-generation biomaterials for tissue engineering applications.…”
Section: Self-assembled Peptide Gels For Cartilage Regenerationmentioning
confidence: 84%